Sob a moldura da tropicália: canções E capas de discos em relações intersistêmicas - Araújo, Luís André Bezerra de (2013)
Tropicalia emerged in late 1967 with the songs ―Alegria, Alegria‖ (Caetano Veloso) and ―Domingo no Parque‖ (Gilberto Gil). But it was in 1968 that the musical movement left his major works recorded. In that year were released records by Tom Zé, Os Mutantes, Caetano Veloso, Gilberto Gil and the collective record Tropicália ou panis et circensis. These albums represented a new moment in the Brazilian Music: opening the explicit cultural dialogues with other countries and with different artistic languages. Our work investigates how was, parallely, turned towards the Brazilian graphic design, from the analysis of the covers of these records, discussing the images with the songs. We started from Luiz Tatit s studies on song and the concept of cultural dialogue according to the Semiotics of Culture.